Peer-to-Peer Lending untuk Pelaku Usaha di Kota Mataram: Analisis Akseptabilitas, Keamanan, dan Biaya - Lukman Effendy; Zuhrotul Isnaini; Isnawati Isnawati (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2026)
The development of financial technology (fintech), particularly Peer-to-Peer (P2P) Lending services, has improved access to financing for Micro, Small, and Medium Enterprises (MSMEs). In Mataram City, the increasing use of these services reflects the growing demand for efficient and secure financial solutions among business actors. This study aims to analyse the factors influencing the intention to use P2P Lending by applying the Technology Acceptance Model (TAM), including perceived ease of use, perceived usefulness, security, and cost. Data were collected from 212 business actors through questionnaires and analysed using PLS-SEM. The results indicate that perceived usefulness and security have a significant influence on usage intention, whereas perceived ease of use and cost do not. These findings suggest that perceived benefits and security assurance are the primary drivers of P2P Lending adoption among MSMEs.